2021
DOI: 10.1016/j.matt.2021.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent suppression of field-induced polarization rotation in relaxor ferroelectric thin films

Abstract: We report a comprehensive study of polarization rotation dynamics in thin films of the prototypical relaxor ferroelectric 0.68PbMg 1/3 Nb 2/3 O 3 -0.32PbTiO 3 . The combination of in operando X-ray diffraction, scanning transmission electron microscopy, and switching dynamics studies reveals the frequency-dependent behavior of polarization evolution and rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…It is worth noting that although the PMNPT thin films exhibit high quality compared with previous studies processing similar thickness, [ 24,54 ] their dielectric constants are still one order of magnitude lower than those in bulk single crystals ( ε 0 = 20 000–28 000 for x = 0–0.32). [ 16–18,46 ] While similar reduced dielectric values had been reported previously in coherently strained PMN‐0.32PT thin films grown on rare‐earth scandate single crystal substrates, [ 54,55 ] which suggests that the suppression of dielectric response observed in thin‐film version could be intrinsic rather than due to the extrinsic effect, such as passive interfacial layer.…”
Section: Resultssupporting
confidence: 71%
“…It is worth noting that although the PMNPT thin films exhibit high quality compared with previous studies processing similar thickness, [ 24,54 ] their dielectric constants are still one order of magnitude lower than those in bulk single crystals ( ε 0 = 20 000–28 000 for x = 0–0.32). [ 16–18,46 ] While similar reduced dielectric values had been reported previously in coherently strained PMN‐0.32PT thin films grown on rare‐earth scandate single crystal substrates, [ 54,55 ] which suggests that the suppression of dielectric response observed in thin‐film version could be intrinsic rather than due to the extrinsic effect, such as passive interfacial layer.…”
Section: Resultssupporting
confidence: 71%
“…Through the analysis of positions and intensities of peaks in diffraction patterns, XRD and ND provide information about the crystalline symmetry, lattice parameters, as well as atomic positions and occupancies. , This information can be further refined by employing techniques such as the Rietveld method . In recent years, XRD and ND have advanced to achieve higher resolutions, increased energies, and compatibilities with in situ characterizations. High-energy X-rays, characterized by their short wavelengths (<0.08 nm or 0.8 Å), can effectively improve the resolution. For instance, for pure PbTiO 3 , Muhtar Ahart et al used high-pressure in situ XRD to confirm the emergence of morphotropic phase boundaries in ferroelectrics by tracking the evolutions of the lattice strain and symmetry .…”
Section: Characterizations Of Lattice Structures and Strainsmentioning
confidence: 99%
“…In situ electrical and mechanical TEM images revealed that the mixed phases were completely converted to pure R or T phases, through the movement of phase boundaries between both phases. Furthermore, by finely controlling the strain levels, mixed M A and M C phases were stabilized in the strained PbMgNbO 3 –PbTiO 3 relaxer film, which could be considered as being a transient state only attained by stimulating electrical films and their bulk counterparts. , During electric field–induced M A –M C transitions, inclined and elongated polar nanodomains coupled with simultaneous polarization rotations contribute to the strong electromechanical response . For chemical pressure–modulated MPBs, e.g., (Bi 0.86 ,Sm 0.14 )­FeO 3 films, the piezoelectric coefficient ( d 33 ) increased by 50% to 110 pm V –1 compared to that of the pure (nonsubstituted) BiFeO 3 film.…”
Section: Strain Engineering In Ferroelectric-based Applicationsmentioning
confidence: 99%
“…In 0.68PbMg 1/3 Nb 2/3 O 3 –0.32PbTiO 3 films, it was found that the multiple polarization orientations persist even at high fields and that the rotation pathway through the M a (monoclinic distortion of R) and M c (monoclinic distortion of T) phases was strongly frequency‐dependent. [ 264 ] X‐ray diffraction, even with a micrometer‐scale spot, can probe the nanoscale structure through diffuse scattering, yet these measurements provide an averaged picture of a complex structure. The recognition that the local coupling of chemical, structural, and polar disorder is critical for understanding relaxors and has driven interest in mapping such disorder with TEM‐based approaches to develop real‐space understanding.…”
Section: New Materials and Epitaxymentioning
confidence: 99%